El consumo bruto de energía primaria en Andalucía (1870-1930) - Fernández-Paradas, Mercedes (Universidad de Málaga. Facultad de Filosofía y Letras, 2009)
Este trabajo estudia el consumo bruto de energía primaria en Andalucía en el contexto español, para el periodo 1870-1930, incluyendo las energías tradicionales (fuerza humana y animal, hidráulica y leña) y las modernas (carbón mineral, hidroelectricidad y petróleo). El artículo se divide en cinco apartados. La introducción señala los objetivos del trabajo. El segundo apartado explica las fuentes y los métodos utilizados para calcular el consumo bruto de energía primaria andaluz y español. El tercero analiza la dotación energética de Andalucía. El cuarto presenta una estimación sobre el consumo bruto de energía andaluz y español en los años 1870, 1900 y 1930. Por último, las conclusiones destacan el moderado crecimiento del consumo energético en Andalucía y el predominio de las energías tradicionales.

This article studies the net consumption of primary energy in Andalusia within the context of Spain, for the period 1870-1930, including traditional forms of energy (energy produced physically by people and animals plus energy produced by water and by firewood) and modern forms of energy (coal, hydro-electricity and oil). The text is divided into five sections. The introduction, which outlines the goals of the article. The second section explains the sources and methods used to calculate the net consumption of primary energy in Andalusia and Spain. The third section analyses the energy resources of Andalusia. The fourth presents an estimate of the net consumption of primary energy in Andalusia and Spain in the years 1870, 1900 y 1930. Finally, the conclusions, which highlight a moderate growth in energy consumption in Andalusia and the predominance of traditional forms of energy.
Keywords: Energía - Andalucía - 1870-1930; Andalucía; Energías tradicionales y modernas; Consumo; Andalusia; Traditional and modern forms of energy; Consumption